The Facial Approximation of the Skull Attributed to Jan Žižka (ca. AD 1360–1424) - Cicero Moraes; Johari Yap Abdullah; Jiri Šindelář; Matěj Šindelář; Zuzana Thomová; Jakub Smrčka; Mauro Vaccarezza; Thiago Beaini; Francesco Maria Galassi (Heritage)
The present study aims to approximate the face from the alleged skull of Jan Žižka (ca. AD 1360–1424), a military commander and national hero in the Czech Republic. Found in 1910, the skull has only a fraction of its original structure, which required an initial effort to reconstruct the missing regions from data collected in CT scans of living people’s heads. The forensic facial approximation consisted of projecting the skin boundaries with soft tissue markers and cross-referencing data from statistical projections from CT scans of living people and the use of the anatomical deformation technique, where the digital head of a virtual donor was adjusted until it matched the alleged skull of the Czech general. The final face was the result of the cross-referencing of all data and the completion of the structure respected the iconography attributed to Jan Žižka.